THE INFLUENCE OF PRODUCT QUALITY AND PROMOTION MIX “R” PT AIR MANCUR OF CONSUMER PURCHASING DECISIONS IN SURAKARTA - Victoria Dian Kartikarini; Sampurno Sampurno; Djoko Wahyono (Faculty of Pharmacy, Universitas Gadjah Mada)
Today the competition in the industry of herbal medicine / jamu tends to increase. PT Air Mancur as a manufacturer of herbal medicine should be able to compete by offering quality herbal medicine and can satisfy consumer desire. In the face of such competition, PT Air Mancur in addition must pay attention to product quality also needs to have promotion mix strategy (promotional mix) is implemented correctly. This study chose Madurasa as a subject studied because Madurasa is a product that produces great profitability for PT Air Mancur. The purpose of this study to determine the effect of product quality and promotion mix of Madurasa purchasing decisions by consumers in Surakarta. This study uses a questionnaire to determine the effect of product quality and promotion mix of the purchase decision. Large sample used in this study based on the formula Aaker and Day with 95 % confidence level is 400 respondents. Engineering samples of the determination of non probability design capture through purposive sampling procedure. Data were analyzed with regression method to determine the effect of product quality and promotion mix of Madurasa purchasing decisions by consumer in Surakarta. The result showed that the variable product quality, advertising, and personal selling them influence on purchase decisions by consumers Madurasa in Surakarta. Meanwhile, sales promotion and public relation not impact on purchasing decisions. Ads have the most significant influence on Madurasa purchase decisions by consumers in Surakarta. Keywords : quality of product, promotion mix, purchasing decisions, Madurasa.